Development of 3D-Printed Vibration Absorbers for Noise Control in Material Removal Processes - Sungmyung Lee; Haewoon Choi; Jonghyun Kim (Machines)
Material removal processes such as milling, drilling, and turning often generate harmful vibrations that can negatively impact both machine performance and operator safety. Addressing these vibrations at their source or reducing them to safe levels is, therefore, a critical challenge. This study proposes a practical solution by introducing thin-fin-type vibration-absorbing devices fabricated using 3D printing technology. These devices are designed specifically to mitigate vibration propagation during milling operations. To evaluate their effectiveness, a multi-sensor system comprising sound level meters, a vibrometer, and a vision–acoustic camera was employed to measure sound levels. The results show that the use of fabricated devices can reduce noise levels significantly, from 93 dB (comparable to power tools or a lawn mower) to 74 dB (similar to normal conversation or a busy office). This substantial reduction demonstrates the potential of the proposed devices to enhance workplace safety and acoustic comfort on the shop floor.